A statistical analysis study on P PackMan Philippines Corporation - Balois, Stephanie; Lapid, Norman; Navarro, Julie (Diliman, Quezon City College of Engineering, 2002)
Packman Philippines Corporation is a subsidiary of VAW Europack. It is one of the leading manufacturers of flexible packaging products in the Philippines. Their products range from satchets to thermoformable food containers and medicine foil labels. The purpose of this study is to determine why 44.52 percent of rejects experienced internally and externally by Packman Philippines Corporation are due to printing defects. Three sets of statistical tests were performed, one for each of three response variables, namely, average readings for temperature, doctor blade pressure, and rubber impression roller (RIR) pressure. For all these response variables, the main factor under study was the machines used in the printing process, with five levels, one for each of the five printing machines. While testing for RIR pressure, an additional factor was added, namely RIR pressure type. The two levels of RIR pressure type are Operator side RIR pressure and Driver side RIR pressure. Therefore, One-Factor ANOVA with Completely Randomized Design for the Fixed Effects Model was used while testing for temperature and doctor blade pressure, while Two-Factor Factorial ANOVA with Completely Randomized Design for the Fixed Effects Model was used to test for RIR pressure. Furthermore, Goodness-of-Fit tests, Duncan's Multiple Range Test, and the Test for Sample Size were included in the design of the experiment, to support the findings of the ANOVA tests, by determining if the normality assumption of the ANOVA tests were fulfilled, to show which differences between various pairs of treatment means were significant and to determine if the sample sizes of the ANOVA tests were sufficient for the tests to be reliable. Also, Residual Analysis was performed to allow for a graphical analysis of the data gathered, and to further determine if the data followed a normal distribution. It was discovered that the mean doctor blade pressures and RIR pressures among the machines were not all equal. Thus, it was concluded that the machines had an effect on the doctor blade pressure and RIR pressure. Further analysis showed that Machine 6 had a significant higher mean doctor blade pressure of 3.53 kPa and that there is a great variability in the mean RIR pressure between the different machines. It is recommended that Packman Philippines Corporation examine Machine 6 for defects affecting its doctor blade, and to examine the rubber impression rollers of all the machines for possible defects. The group also recommends that regular maintenance and inspections be performed on the printing machines to lessen the instances of rejections attributable to printing error caused by incorrect doctor blade or RIR pressure.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 28 : Statistical Analysis for Industrial Engineering
Keywords: Statistics